Thickness-dependent patterning of MoS2 sheets with well-oriented triangular pits by heating in air - Yakobson, Boris I. (2013)
Patterning ultrathin MoS2 layers with regular edges or controllable shapes is appealing since the properties of MoS2 sheets are sensitive to the edge structures. In this work, we have introduced a simple, effective and well-controlled technique to etch layered MoS2 sheets with well-oriented equilateral triangular pits by simply heating the samples in air. The anisotropic oxidative etching is greatly affected by the surrounding temperature and the number of MoS2 layers, whereby the pit sizes increase with the increase of surrounding temperature and the number of MoS2 layers. First-principles computations have been performed to explain the formation mechanism of the triangular pits. This technique offers an alternative avenue to engineering the structure of MoS2 sheets.